A Framework to tackling the synchrony between Social and Ecological phases of the annual cyclic movement of transhumant pastoralism - Perez Leon, Natalia; Bruzzone, Octavio Augusto; Easdale, Marcos Horacio (MDPI, 2020)
Transhumant pastoralism is mobile livelihood strategy in which families and their herds move seasonally from lowlands, where they settle during the winter, towards the highlands, located in mountainous areas, during the summer. We propose a framework, rooted in a socio-environmental coevolutionary perspective, for the transhumant annual cycle as comprised by the winter-phase, the summer-phase, and movement transitions between them. The aim was to assess the level of synchrony between ecological phases and social phases and the benefit of moving between pasturelands in selected study cases from Patagonia, Argentina. Ecological phases were addressed by the diference between vegetation productivity of winter- and summer-lands, with Fourier transform applied to data series of the Normalized Difference Vegetation Index (NDVI). Social phases were estimated by the proportion of annual time spent by pastoralists and their herds in each site and during transitions, respectively, obtained from interviews. The framework was sensitive to capturing diferences across study cases. There was an observed tendency towards more synchronisation in the cases with closer distances and asynchrony in the cases with longer distances and longer movement transitions between pasturelands. Results are encouraging as a step towards the development of a monitoring system of both transhumant pastoralism activity and environmental changes.